Archivos e investigaciones territoriales. Acerca de la literatura misionera y sus autores (La Rivada, 2024)
This article presents the main results and contributions by a research team that has extensive experience in approaching the literature of Misiones, and in the construction of authorial archives, both physical-material and digital-virtual. Firstly, we discuss the basic postulates that theoretically and methodologically support the constructed archives, in dialogue with/ taking into account o simplemente using the categories definded collectively: “literature” and “territorial authors”. Then, the actions carried out for the recovery, organization, digitization and circulation of these files are specified.
Keywords: Literature; Territory; Authors; Archive